Sclerosing mesenteritis as a rare cause of upper ileus - Bezmarević, Mihailo; Mirković, Darko; Perišić, Nenad; Cerović, Snežana; Panišić, Marina; Micković, Saša; Tufegdžić, Ivana; Mitrović, Jelena; Djordjević, Zoran (Vojnosanitetski pregled, 2013)
Introduction. Sclerosing mesenteritis is a rare pathological entity characterized by non-specific tumor-like expansion in mesentery. Accurate diagnosis of this disease is rarely made preoperatively. Surgery takes place in diagnosis, as well in treatment of the disease. We presented a case of sclerosing mesenteritis that affected the final portions of duodenum and initial part of jejunum with clinical picture of upper gastrointestinal obstruction. Case report. A 46-year-old man without previous medical history was presented with vomiting and loss of weight in the last 6 months. Due to suspicion of  parapancreatic tumor by CT examination and clinical presentation of the disease, the patient underwent laparotomy. A mass infiltrated mesenteric root, initial part of superior mesenteric artery, the fourth duodenum portion and the ligament of Treitz, while the stomach and duodenum were dilatated. The intraoperative biopsy indicated a benign process. The mass was reduced with desobstruction of the duodenum. Definitively, histopathological finding showed fibromatosis in different phases of activity. Postoperative course passed without complications. The patient continued to receive an immunosuppressive drug therapy. After a 6-month treatment the patient showed no gastrointestinal problems. Conclusion. Sclerosing mesenteritis that affects the duodenum and the proximal part of the jejunum with subacute upper gastrointestinal obstruction is an extremely rare condition. In the presented case a surgical procedure was necessary for marking the diagnosis and treatment as well.
Keywords: panniculitis; peritoneal; intestinal obstruction; diagnosis; surgical procedures; operative; treatment outcome